Esophageal Motility Disorders and Diverticula: Physiologic Implication and Surgical Considerations. Issue 3 (September 2021) - Sudarshan, Monisha; Murthy, Sudish
Zenker's diverticula are the most common diverticula of the esophagus and attributed to a hypertensive non-compliant cricopharyngeus muscle with reduced sphincter opening. Cricopharygeus myotomy is the treatment with variable management of the diverticulum. Mid-esophageal diverticula are classically attributed to traction, though many are associated with dysmotility similar to epiphrenic/distal esophageal diverticula. Myotomy is again key for symptomatic presentations. Resection of the diverticula and a partial fundoplication are other components in the surgical management. Although treatment of diverticula has evolved over the decades, it remains a rare condition often associated with significant pre-operative symptomatology and post-operative morbidity.